Mindfulness- and compassion-based interventions for family carers of older adults: A scoping review - Murfield, Jenny; Moyle, Wendy; O'Donovan, Analise (International journal of nursing studies, 2021)
To provide an overview of the current use of mindfulness- and compassion-based interventions with family carers of older adults, to aid primary healthcare practitioners in their decision-making around referral to wider healthcare services. The study was guided by four research questions: what interventions are currently used; whom they are used with; why they are used; and their evidence-base in terms of acceptability and effectiveness. A scoping study using the methodological frameworks of Arksey and O'Malley and Levac et al. Searches of electronic databases (MEDLINE, CINHAL, PsycINFO), reference lists of relevant articles, and journal websites were conducted in June 2019. Search terms were developed via an iterative process, and included medical subject headings and keywords relating to mindfulness and compassion, interventions, and family carers. Articles were included if: written in English; published in a peer-reviewed journal; employed quantitative, qualitative, or mixed-method research designs; and described a mindfulness- and/or compassion-based intervention for adults identified as a family carer of an older adult. Data from included studies were charted (using a purposively-designed template), and descriptively analysed in relation to the study's research questions. From 2005 unique records, 32 primary studies were included. Seven types of mindfulness- or compassion-based interventions were broadly described within studies, including: mindfulness-based stress reduction (n = 13), mindfulness-based cognitive therapy (n = 3), meditation interventions (n = 9), acceptance and commitment therapy (n = 1), dialectical behaviour therapy (n = 1), compassion-focused therapy (n = 1), and study-specific interventions involving a combination of mindfulness and/or compassion (n = 4). Studies sampled a total of n = 991 participants and targeted six family carer sub-groups: dementia (n = 23), cancer (n = 5), amyotrophic lateral sclerosis (n = 1), chronic conditions (n = 1), cirrhosis (n = 1), and Parkinson's disease (n = 1). A variety of health outcomes were assessed across interventions, with the most common being depression (n = 26), anxiety (n = 15), burden (n = 15), quality of life (n = 14), and stress (n = 11). The evidence-base for each intervention was insufficient and too heterogeneous to make clear statements regarding effectiveness. However, based on these findings, interventions show some potential utility in supporting family carers in their role and, given a collective rate of attrition (18%), may do so in a way that is acceptable to carers. This scoping study highlighted the nascent use of mindfulness- and compassion-based interventions with family carers of older adults, and provided important substantive detail about what each intervention entails. Based on current evidence, a number of implications for research and practice are presented.